Prospective study of surgical site infections post-open esophageal cancer surgery, and the impact of care bundles. Issue 12 (16th February 2021) - Raftery, Nicola B; Murphy, Conor F; Donlon, Noel E; Heneghan, Helen; Donohoe, Claire L; King, Sinead; O'Connell, Brian; Ravi, Narayanasamy; Reynolds, John V
Summary: SSIs represent common infection-related morbidity following major surgery. Modern care bundles have been established as prophylactic measures aimed at preventing SSI occurring postoperatively. SSI incidence and data on common culprit pathogens post-esophagectomy for cancer have not been previously reported. Patients (2013–2018) treated with curative intent were studied. SSI was defined as per the Center for Disease Control (CDC) definition. A care bundle pathway following the National Institute for Clinical Excellence (NICE) guidelines for prevention of SSIs was introduced in 2013 and was audited quarterly. Risk factors and associations of SSIs were analyzed, as was the prevalence of isolated pathogens. Multivariable logistic regression examined independently predictive factors of SSIs and oncologic outcomes. Of 343 patients, 34 (9.9%) developed a postoperative SSI, with a median (range) of 8 (6–17). Quarterly audit carried out over 6 years showed no significant annual variance or trend. The most prevalent pathogen cultured was Methicillin-sensitive Staphylococcus aureus ( MSSA ) in nine patients (32%) followed by Candida albicans (29%), Escherichia coli (14%), and Enterococcus faecium (11%). SSI was significantly associated with pneumonia ( P = 0.001), respiratory failure ( P = 0.014), atrial fibrillation ( P = 0.004), anastomotic leak ( P < 0.001), and in-hospital blood transfusions ( P = 0.031). SSI did not impact the overall survival ( P = 0.951). SSI rates can be maintained at less than 10% using strict care bundles and regular audit. The most common culprit pathogen is gram-positive MSSA representing 32% of cases. These data are novel and may represent a modern benchmark for SSI post-open esophagectomy for cancer. This study highlights the incidence and associations of SSI post-esophageal cancer surgery.